Control Strategy for Solar Energy-Saving Lamps for Optimized Energy Utilization and Sustainability of Operation Durability: Indonesia Case - Halimi, Burhanuddin; Purwadi, Agus; Heryana, Nana (UI Scholars Hub, 2022)
To solve the electrification ratio issue, the Indonesian government has promoted the use of solar energy-saving lamps. This study proposes a control strategy that adopts current reference time-based profiling for solar energy-saving lamps. For optimal energy consumption, the current reference profile is determined according to users’ daily energy requirements. From the aspect of user comfort, a gradual step reference profile is also introduced to provide a subtle change in lighting intensity level. The proposed control strategy can minimize energy consumption and optimize the operation durability of the system. The concept is verified by simulating four scenarios, the results of which demonstrate the effectiveness of the proposed control strategy. Computational simulation results indicate that Scenarios C and D which adopt the proposed time-based profiling can respectively reduce the daily energy consumption of the conventional control strategy by 47.14% and 39.79%, respectively. In terms of durability in providing electricity, both scenarios can continue to supply electrical power for two days without any solar irradiance. The proposed method can also improve customer service through the comfort provided in Scenario D.